Slow component of VO2 during level and uphill treadmill running: relationship to aerobic fitness in endurance runners - reis, vm (2007)
Aim. The aim of this study was to compare the oxygen uptake (VO2) slow component (SC) during level and uphill running in endurance runners, and to identify associations between the SC and the following aerobic fitness indicators: peak VO2, running speed associated with the peak VO2 (Vpeak), running speed at the lactic threshold and the VO2 fraction elicited at the lactic threshold. Methods. Fourteen male endurance-trained runners underwent several 6-min bouts of level (LTR) and 10.5% uphill treadmill running. VO2 SC was calculated as the difference between mean VO2 during the 6(th) and the 3(rd) minutes. Results. The highest mean values for the SC were 181.9 +/- 240.2 mL.min(-1) for level running at similar to 94% peak VO2 and 105.4 +/- 154.6 mL.min(-1) for uphill running at similar to 90% peak VO2. The SC observed during the last bout of the LTR correlated with peak VO2 and with Vpeak (-0.71 and -0.76, P<0.05, respectively). Conclusion. The results show that for endurance-trained runners the magnitude of the SC is not affected by the treadmill gradient and that within a homogeneous sample of endurance-trained runners the SC does not correlate with indicators of aerobic fitness.